The Importance of Constructivism and Constructivist Pedagogy For Disability Studies in Education - Deborah J. Gallagher (Disability Studies Quarterly, 2004)
Many in disability studies approach disability as a culturally constructed experience, owing its existence to the beliefs and practices built around how any given society responds to human difference. This approach is predicated on the belief that all knowledge is socially constructed. But what does this perspective mean for educators in their daily classroom teaching practices? I address this question by examining the practical implications of disability studies scholarship from a constructivist perspective. In so doing, I offer insights into how the constructivist perspective alters not only our understanding of individual differences, but also its potential for changing teaching practices.